Pengaruh Variasi Produk Terhadap Keputusan Pembelian Konsumen Pada Toko Snugstore Medan - Hafiza Adlina (Jurnal Niaga & Bisnis (e-journal), 2015)
This study aimed to analyze the effect of product variety on consumer purchasing decisions in Snugstore . This research is a form of associative method with a quantitative approach with a view to find how much influence between the variables X is Product Variations to variable Y is the consumer purchase decision.  Based on the analysis results of SEM ( Structural Equation Modeling ) indicates that the variable X4 or size of a product is part of the X variables that influence purchase decisions in the store Snugstore field . Size is divided into two items that measure the completeness and appropriateness of the size of the consumer Demand , both items are positive and become advocates for the high influence of the size of the products on consumer purchasing decisions . Based Goodness of Fit table above, it is known that the p-value ≥ 0:05 , this means that the alternative hypothesis is accepted and the null hypothesis is rejected that there are significant variations in the product on consumer purchasing decisions on Snugstore . RMSEA value ie RMSEA ≤ 0.05 ≤ 0.08 indicate that the model is a good fit . Value Std . RMR is this Std.RMR ≤ 0:05 shows that the model has good Goodness of Fit . Value indicates that GFI GFI ≥ accepted . Keywords : Product Variation, Consumer Purchase Decisions.